Letter: association between the risk of microscopic colitis and use of proton pump inhibitors. Issue 4 (31st July 2021) - Liu, Yuanbin; Chen, Mingkai
LINKED CONTENT: This article is linked to Zylberberg et al paper. To view this article, visit https://doi.org/10.1111/apt.16363